Kearifan Lokal Dalam Mitigasi Bencana Banjir Berulang Yang Terjadi di Kecamatan Karanganyar Demak Tahun 2024 - Clara Hilaria Valentina Saputra; Neny Marlina (Journal of Politic and Government Studies, 2026)
This study examines the recurring floods that occurred in Karanganyar District, Demak Regency, in 2024, specifically in Ketanjung Dukuh Norowito Village. This study demonstrates the need for disaster mitigation efforts that focus not only on structural approaches but also accommodate the local wisdom of the community. This study aims to analyze the role of local wisdom as a social phenomenon that supports mitigation decision-making and its success, and to determine whether the government's response to recurrent flooding is beneficial for mitigation. The researchers also examine whether the "sedekah bumi" (earth alms) program creates conflict or is aligned with government officials. The theory used is Disaster Mitigation in the book "Response to Natural Disaster Emergency" by Giri (2017). The study employed a descriptive qualitative method with data collection techniques through interviews, observation, and documentation, involving informants including flood-affected communities, local leaders, and relevant government actors. The results indicate that local wisdom, such as mutual cooperation (gotong royong), local knowledge, deliberation, and sedekah bumi (earth alms) play a significant role in improving community preparedness. This point of synergy in mitigation is realized through the integration of local knowledge in detecting natural signs with local government infrastructure policies. This collaboration effectively increased the success of short-term mitigation, particularly in accelerating evacuation response times and strengthening social solidarity at the Karanganyar District level. Although the role of traditional leadership has shifted to hamlet heads and has not yet been fully incorporated into written policies, collaborative practices remain a key supporter of social resilience and program sustainability. Based on these findings, it can be emphasized that the synergy between local wisdom and government efforts is a key factor in increasing the effectiveness of recurrent flood mitigation in Ketanjung Village, Karanganyar District, Demak Regency. Further research is recommended to assess long-term effectiveness and develop quantitative methods for more precise flood risk mapping.